The impact of community development projects in sustaining the livelihoods of the communities in Lepelle-Nkumpi Local Municipality in Limpopo Province, South Africa - Letsoalo, Pheagane Klass (My University, 2019)
Development projects have been widely implemented in South Africa and the rest of the world in order to promote social and economic development. While many projects generate some income for beneficiaries, when they are assessed within the broader context of the meaning of development, it is not so clear if, in fact, they have made such impact. In its efforts to reduce poverty and unemployment and to grow the local economy, Lepelle-Nkumpi Municipality has implemented many community development projects. While the municipality has used its Integrated Development Plans (IDPs) to support such projects, the impact on the livelihoods of beneficiaries does not appear to be as pronounced. The aim of this study was therefore to assess more systematic and greater depth, the impact of community development projects in sustaining the livelihoods of communities in Lepelle-Nkumpi Local Municipality in Limpopo Province. The study was based on mixed methods research design where a small sample of nine beneficiaries from five different types of projects (crop farming, poultry farming, early childhood development (ECD) and tourism), and two municipal officials or other stakeholders were interviewed. Interviews were used to collect primary data from the respondents, and secondary data was collected from sources such as IDP reports, journals and articles. The Sustainable Livelihoods Framework was adopted as the theoretical lens for the analysis of selected projects. The findings from the study indicate that although beneficiaries of projects that were studied benefited in terms of income and employment, project interventions had a limited impact because they did not lead to any significant acquisition of assets by beneficiaries. The income was also deemed to be insufficient for the needs of the participants. Furthermore, there was no evidence that the beneficiaries were empowered by the projects. Key words: Livelihoods; projects, development, sustainability, capability.
Thesis (MDEV. (Planning and Management)) -- University of Limpopo, 2019
Keywords: Livelihoods; Projects; Development; Sustainability; Capability; Community development; Sustainable development